2014
DOI: 10.4081/ijas.2014.3483
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localisation of Phospholipid Hydroperoxide Glutathione Peroxidase in Bull’s Spermatogenic Cells

Abstract: Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is a selenoprotein, which protects biomembranes from oxidative damages, and it also accounts for almost the entire selenium content of mammalian testis. The present investigation was performed to localise PHGPx in the testis and in epididymal and ejaculated spermatozoa of the bull by using light and electron immunomicroscopy. The study also aimed to further clarify the possible functions of the protein in bull fertility. In the testis, spermatogenic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
2
8
0
7
Order By: Relevance
“…Similarly, immuno-signals were also observed in the epididymal and ejaculated sperm particularly in acrosome region. These dynamic strong signals at different stages of sperm maturation conform to the earlier biochemical observations indicating that GPX4 is essential for the optimal development and function of bovine sperm similar to other mammalian species [70].…”
Section: Important Selenoproteins Relevant To Male Reproductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, immuno-signals were also observed in the epididymal and ejaculated sperm particularly in acrosome region. These dynamic strong signals at different stages of sperm maturation conform to the earlier biochemical observations indicating that GPX4 is essential for the optimal development and function of bovine sperm similar to other mammalian species [70].…”
Section: Important Selenoproteins Relevant To Male Reproductionsupporting
confidence: 87%
“…In addition to these evidences, recently Parillo and colleagues [70] reported that strong expression signals of GPX4 protein were observed in seminiferous tubules (apical region) of healthy Chianina bulls, where it was localized in the cytoplasmic region of maturing sperm i.e., spermatogonia, round spermatids, and elongated spermatids. Similarly, immuno-signals were also observed in the epididymal and ejaculated sperm particularly in acrosome region.…”
Section: Important Selenoproteins Relevant To Male Reproductionmentioning
confidence: 97%
“…When Se concentrations are low during the final stages of spermatogenesis, GPX4 activity is decreased, leading to higher concentrations of active peroxides that can cause oxidative injury that can accumulate and lead to delayed viability impairment [ 33 ]. Moreover, Parillo et al [ 34 ] reported that strong expression signals of GPX4 protein were observed in the apical region of seminiferous tubules in bulls. These dynamic signals at different stages of sperm maturation suggest that GPX4 is essential for optimal bovine sperm development and function and that Se deficiency may lead to impaired spermatogenesis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Parillo et al [ 34 ] reported that strong expression signals of GPX4 protein were observed in the apical region of seminiferous tubules in bulls. These dynamic signals at different stages of sperm maturation suggest that GPX4 is essential for optimal bovine sperm development and function and that Se deficiency may lead to impaired spermatogenesis [ 34 ]. However, this last phase of spermatogenesis in bulls lasts 17 days; therefore, the concentration of microelements measured in the blood serum on the day of sperm collection could not truly be correlated with spermatogenesis itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation